Investigating the biogeochemistry of the Mozambique Channel thermocline using an optimum multiparameter analysis approach - Harris, Eesaa (Department of Oceanography, 2023)
The ocean's thermocline represents the transition zone between the surface and deep ocean. Its formation is linked to vertical and horizontal diffusion, and it constitutes part of the ocean's wind driven circulation, playing a critical role in the lateral advection and vertical supply of nutrients. In the Indian Ocean, the topography, winds, and inter-ocean exchange make the basin's thermocline unique. Particularly complex thermocline circulation occurs in the Mozambique Channel, the highly dynamic region between the coast of south eastern Africa and Madagascar, owing to the confluence of tropical and subtropical regimes in the southwestern Indian Ocean. Our current understanding of the Mozambique Channel thermocline is largely derived from hydrographical analyses (i.e., conservative property relationships such as temperature-salinity), which do not resolve the influence of mesoscale features such eddies on the regional biogeochemistry. Additionally, the Mozambique Channel is one of the three source regions to the Agulhas Current, such that its biogeochemistry may influence the waters of this western boundary current. Here, the thermocline array approach within the optimum multiparameter (OMP) analysis framework was used to determine the contributions of different source waters to the thermocline across four transects sampled in the southwestern Indian Ocean, one at either end of the Mozambique Channel and two across the upper Agulhas Current. Three thermocline source regions proximate to the Mozambique Channel were identified (equatorial, tropical and subtropical) and used to initialise the OMP analysis. This localised approach was validated by the low standard deviations (average <20%) associated with perturbing the model parameters in a Monte Carlo analysis and the low residuals (average < 5%) associated with the model solution, allowing for an evaluation of relative biogeochemical changes across the region. A decline in the upper thermocline nutrient concentrations between the source regions and the transects can be explained by mixing with nutrient-deplete surface waters. By contrast, an increase in the nutrient concentrations of the thermocline evinces in situ remineralization, presumably following primary productivity in Mozambique Channel surface waters. The presence of tropical waters across the two Agulhas transects confirms a supply of tropical nutrients to the current, with the coincidence of significant tropical water contributions (up to 60%) and mesoscale eddies suggesting that these features represent a mechanism by which tropical thermocline water is supplied to the Agulhas Current region. A rise in the thermocline nitrate-to-phosphate ratios across the Agulhas transects but not in the Mozambique Channel transects indicates that nitrogen is added to the Agulhas Current region by local N2 fixation occurring in the subtropical waters south of the Mozambique Channel (25°S). This finding contradicts recent suggestions that the channel itself is a hotspot for N2 fixation. The fact that the OMP analysis applied at the regional scale captures the complexity and heterogeneity of the southwest Indian Ocean indicates that this approach can be used to quantitatively assess thermocline contributions to shallow nutrient cycling in hydrodynamically complex regions.